Treatment of familial hypercholesterolaemia in children and adolescents in the last three decades. (10th May 2013) - Elis, Avishay; Zhou, Rong; Stein, Evan A.
Abstract Background: This study evaluated the effectiveness of long-term intensive lipid-lowering therapy in children and adolescents with familial hypercholesterolaemia. Methods: The charts of 89 children and adolescents with heterozygous familial hypercholesterolaemia among ∼1000 patients treated from 1974 to 2008 were reviewed. Familial hypercholesterolaemia was defined as low-density lipoprotein cholesterol level >90th percentile in individuals with a history of familial hypercholesterolaemia. Results: Of the 89 patients, 51% were male; the mean age at diagnosis was 8 ± 4 years, and the mean follow-up was 13 ± 8 years. Baseline and most recent low-density lipoprotein cholesterol levels (mg/dl) under treatment were 250 ± 50 and 142 ± 49, respectively, reduced 43% from baseline (p < 0.0001). At the most recent visit, 39 patients received statin monotherapy, mainly atorvastatin or rosuvastatin, and 50 (56%) patients received combination therapy, mainly vytorin or rosuvastain/ezetimibe, 15 patients were >30 years of age, and none developed symptomatic cardiovascular disease or needed revascularisation. Conclusions: Long-term statin-based therapy can reduce low-density lipoprotein cholesterol levels in most children and adolescents with heterozygous familial hypercholesterolaemia and decrease cardiovascular risk significantly.